2009
DOI: 10.1111/j.1582-4934.2008.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 modulates neutrophil recruitment to the lung

Abstract: Transmigration of neutrophils through the microvascular endothelium is a cardinal event of acute inflammation. It has been suggested that gap junctions made of connexin43 (Cx43) may serve as a conducting pathway to spread inflammatory signals within the lung capillary network. To determine whether Cx43 contributes to neutrophil transmigration in vivo, the number of transmigrated neutrophils was monitored in lungs of Cx43 mouse models subjected to inflammation by intratracheal instillations of Pseudomonas aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 30 publications
3
102
1
Order By: Relevance
“…Cytoplasmic dye transfer experiments and compatible electron microscopy ( Figure 2) have also suggested possible endothelial GJIC with recruited neutrophils (23,26). Surprisingly, inflammatory insults generally attenuate GJIC (26,53), despite an increase in the connexin content of cells in the distal lung (18,54). This discordance may arise from the inflammatory internalization of endothelial connexin 43 (50).…”
Section: Neutrophils Adherent To the Vascular Endothelial Surfacementioning
confidence: 89%
See 1 more Smart Citation
“…Cytoplasmic dye transfer experiments and compatible electron microscopy ( Figure 2) have also suggested possible endothelial GJIC with recruited neutrophils (23,26). Surprisingly, inflammatory insults generally attenuate GJIC (26,53), despite an increase in the connexin content of cells in the distal lung (18,54). This discordance may arise from the inflammatory internalization of endothelial connexin 43 (50).…”
Section: Neutrophils Adherent To the Vascular Endothelial Surfacementioning
confidence: 89%
“…The loss of endothelial connexin 43 was associated with an attenuation of leukocyte adhesion in the cremasteric microcirculation (55). Concordantly, proinflammatory effects of pulmonary connexin 43 were observed, although these findings were thought to reflect endothelial-endothelial GJIC (54). Conversely, an in vitro study using human umbilical vein endothelial cells reported that gap junction blockade augmented neutrophil transmigration (26).…”
Section: Neutrophils Adherent To the Vascular Endothelial Surfacementioning
confidence: 89%
“…In support of this idea, we found that the inhibition of GJIC by well-known GJBs, including the 43 Gap26 mimetic peptide for Cx43, fully prevented the activation of CFTR current. 43 Gap26 is an analogue to part of the amino-acid sequence of the first extracellular loop of Cx43, and is known to inhibit Cx43-mediated cell-to-cell communication by preventing docking gap junction channels in airway cells (24,33,34). Finally, the inhibition of GJIC resulted in ASL volume collapse in the presence of PGE 2 , not only in Calu-3 cells but also in primary cultures of well-polarized HAECs grown at the air-liquid interface.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, they participate in the regulation of almost every step of the inflammatory response, including antigen presentation, chemokine and cytokine production, inflammatory cell migration, adhesion, and activation (12)(13)(14)(15)(16)(17). On the other hand, the proinflammatory mediators LPS, TNF␣, and NO have been identified as potent regulators of GJs in a variety of cell types (14, 18 -23).…”
mentioning
confidence: 99%